Effects of Nb additions and heat treatments on the microstructure, hardness and wear resistance of CuNiCrSiCoTiNbx high-entropy alloys - Avila Salgado, Denis Ariel; Juárez Hernández, Arturo; Lara Banda, María del Refugio; Bedolla Jacuinde, Arnoldo; Guerra, Francisco V. (Multidisciplinary Digital Publishing Institute, 2022)
Abstract: In this research, a set of CuNiCrSiCoTi (H-0Nb), CuNiCrSiCoTiNb0.5 (H-0.5Nb) and CuNiCrSiCoTiNb1 (H-1Nb) high-entropy alloys (HEAs) were melted in a vacuum induction furnace. The effects of Nb additions on the microstructure, hardness, and wear behavior of these HEAs (compared with a CuBe commercial alloy) in the as-cast (AC) condition, and after solution (SHT) and aging (AT) heat treatments, were investigated using X-ray diffraction, optical microscopy, and electron microscopy. A ball-on-disc configuration tribometer was used to study wear behavior. XRD and SEM results showed that an increase in Nb additions and modification by heat treatment (HT) favored the formation of BCC and FCC crystal structures (CS), dendritic regions, and the precipitation of phases that promoted microstructure refinement during solidification. Increases in hardness of HEA systems were recorded after heat treatment and Nb additions. Maximum hardness values were recorded for the H-1Nb alloy with measured increases from 107.53 HRB (AC) to 112.98 HRB, and from 1104 HV to 1230 HV (aged for 60 min). However, the increase in hardness caused by Nb additions did not contribute to wear resistance response. This can be attributed to a high distribution of precipitated phases rich in high-hardness NiSiTi and CrSi. Finally, the H-0Nb alloy exhibited the best wear resistance behavior in the aged condition of 30 min, with a material loss of 0.92 mm3.